Endurance cyclist fluid intake, hydration status, thirst and thermal sensations: gender differences - Armstrong, L. E.; Johnson, E. C.; McKenzie, A. L.; Ellis, L. A.; Williamson, K. H. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
This field investigation assessed differences (e.g., drinking behavior, hydration status, perceptual ratings) between female and male endurance cyclists who completed a 164-km event in a hot environment (35 °C mean dry bulb) to inform rehydration recommendations for athletes. Three years of data were pooled to create 2 groups of cyclists: women (n = 15) and men (n = 88). Women were significantly smaller (p < .001) than men in height (166 ± 5 vs. 179 ± 7 cm), body mass (64.6 ± 7.3 vs. 86.4 ± 12.3 kg), and body mass index (BMI; 23.3 ± 1.8 vs. 26.9 ± 3.4) and had lower preevent urinary indices of hydration status, but were similar to men in age (43 ± 7 years vs. 44 ± 9 years) and exercise time (7.77 ± 1.24 hr vs. 7.23 ± 1.75 hr). During the 164-km ride, women lost less body mass (-0.7 ± 1.0 vs. -1.7 ± 1.5 kg; -1.1 ± 1.6% vs. -1.9 ± 1.8% of body weight; p < .005) and consumed less fluid than men (4.80 ± 1.28 L vs. 5.59 ± 2.13 L; p < .005). Women consumed a similar volume of fluid as men, relative to body mass (milliliters/kilogram). To control for performance and anthropomorphic characteristics, 15 women were pair matched with 15 men on the basis of exercise time on the course and BMI; urine-specific gravity, urine color, and body mass change (kilograms and percentage) were different (p < .05) in 4 of 6 comparisons. No gender differences were observed for ratings of thirst, thermal sensation, or perceived exertion. In conclusion, differences in relative fluid volume consumed and hydration indices suggest that professional sports medicine organizations should consider gender and individualized drinking plans when formulating pronouncements regarding rehydration during exercise